2009
DOI: 10.1007/s10682-009-9313-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent local adaptation of sockeye salmon to glacial spawning habitats

Abstract: Salmonids spawn in highly diverse habitats, exhibit strong genetic population structuring, and can quickly colonize newly created habitats with few founders. Spawning traits often differ among populations, but it is largely unknown if these differences are adaptive or due to genetic drift. To test if sockeye salmon (Oncorhynchus nerka) populations are adapted to glacial, beach, and tributary spawning habitats, we examined variation in heritable phenotypic traits associated with spawning in 13 populations of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 78 publications
1
31
1
Order By: Relevance
“…Ramstad et al [36] found that increased turbidity correlated with longer snouts in breeding adults and females having pink body coloration as opposed to red. These attributes are attributed to reduced visibility.…”
Section: Intra-annual Trends In Lake Clark Water Claritymentioning
confidence: 99%
See 3 more Smart Citations
“…Ramstad et al [36] found that increased turbidity correlated with longer snouts in breeding adults and females having pink body coloration as opposed to red. These attributes are attributed to reduced visibility.…”
Section: Intra-annual Trends In Lake Clark Water Claritymentioning
confidence: 99%
“…These attributes are attributed to reduced visibility. Sexual signaling via red body color is less effective in turbid waters and therefore an unnecessary use of valuable carotenoids [36]. Pink coloration could make spawning fish less visible to predators [36].…”
Section: Intra-annual Trends In Lake Clark Water Claritymentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of wild salmonids to date have used the variation in heritable phenotypic traits that are easily measured (e.g., reproductive timing, adult size, and flesh color) and compared with the variation at neutral genetic markers (e.g., O'Malley et al 2010;Ramstad et al 2010). While informative, these studies are constrained by the limited number of easily measured phenotypic traits known to be highly heritable.…”
Section: Adaptive and Neutral Studies In Natural Populationsmentioning
confidence: 99%